Optimization Of Urine Protein Examination In 5% Acetic Acid Solution And Vinegar Acid Solution - Ahmad Jais; Hepiyansori Hepiyansori; Yurman Yurman; Widia Safitri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
A research has been carried out with the title Optimizing urine protein examination in a 5% acetic acid solution and vinegar acid solution. The study was conducted from April to June 2019. The aim of the study was to see the ability of the vinegar solution in examining urine protein. This research method is the experiment to see the ability of vinegar and acetic acid in the protein denaturation process. The results showed that the results of examining urine protein using 5% acetic acid solution with kitchen vinegar solution. There was no significant difference between the results of examining urine protein with 5% acetic acid solution and kitchen vinegar solution. Where t count 0.067 t table 6.63.